Stepwise Algorithmic Approach to Endoscopic Removal of Biliary Partially Covered and Uncovered Self-Expanding Metal Stents - Deepanshu Jain; Assaf Stein; Muhammad K. Hasan (Korean Society of Gastrointestinal Endoscopy, 2021)
Self-expanding metal stents play a crucial role in the management of patients with biliary obstruction. Endoscopic extraction of uncovered metal stents (UCMSs) and partially covered metal stents (PCMSs) could be challenging because of tissue ingrowth. No standardized technique can guarantee universal success. We present our technique and experience of endoscopic extraction of biliary stents in two patients with a UCMS and three patients with a PCMS. Three of the five patients had a previous failed attempt of stent extraction at an outside hospital. Overall, our composite success rate was 80% (4/5). The individual success rate was 100% (3/3) for PCMSs and 50% (1/2) for UCMSs. The stent-in-stent technique, in which a fully covered metal stent is placed through an existing UCMS/PCMS, was used in 60% (3/5) of the cases, with a success rate of 66.7% (2/3). We share our algorithmic approach to each case, with detailed emphasis on the technical aspects of the procedure.